Raptor and the importance of traffic accidents: Raptor y la importancia de accidentes de tránsito - Ulloa-Ordoñez, Lucia Victoria (2023)
Mr. Editor of the Revista de la Facultad de Medicina Humana, Lima, Peru I am writing to you, in relation to the review article "Association between the time of pre-hospital care and hospital mortality in victims of traffic accidents" published in 2020 Volume 20, number 01.In the aforementioned work, by M.J.G. Fernandez Sandoval et al., highlight the existence of a significant association between the time of prehospital care and mortality, with which I agree and express that it is of vital importance, even a good level of prehospital education can be applied in the specific topic of traffic accidents, since it represents an important health problem and is a priority in research.